Approaching the gender perspective: fashion in international trade or mere rhetoric? - Solano, Gerald (Latin American Journal of Trade Policy, 2024)
The link between trade and gender is complex and multifaceted, since not all societies understand it in the same way or present the same asymmetries. Besides, international trade and economic globalization have a significant impact on the way societies treat gender equality and how people experience it in different spaces and contexts, which undoubtedly presents great challenges. The concept of gender perspective has emerged as a crucial conceptual framework in a variety of academic and practical fields, including, but not limited to, the field of international trade; Therefore, the main objective of this article is to describe the theoretical-conceptual approach to the link between trade and gender, understood it, in its traditional form, as synonymous of women, and also its benefits and challenges. In this article, a descriptive and descriptive-explanatory approach was used as a method and technique, which sought to establish the relation and correlation between the variables under study, through a bibliographic review of primary and mainly secondary sources to obtain as results an approach of key concepts of the link between trade and gender. The gender perspective challenges traditional, hegemonic, and homogeneous visions of the world, promoting instead inclusion, equity and respect for human diversity in all its forms; International trade and economic globalization for their part have a significant impact on the way societies treat gender equality and how people experience it, the challenges are still quite a few.